Wetland restoration, household income, and livelihood structure of farmers - Feng, Ji; Wen, Yali; Zhang, Huiyuan; Duan, Wei; Hao, Haiguang (Frontiers in Sustainable Food Systems, 2024)
Background Wetland restoration is an important measure for restoring wetland ecosystems and their ecological benefits, with the goal of restoring their ecological functions and resources. However, wetland restoration affects farmers' incomes and livelihoods. Although existing research has contributed to a deeper understanding of the relationship between wetland restoration and farmers' household incomes, some issues require further consideration. Therefore, here, we aimed to analyse the impact of wetland restoration on farmers' incomes and provide empirical evidence for the coordination mechanism of protection and development in the Poyang Lake Wetland in Jiangxi Province. Methods Based on 2 years of balanced panel data of 365 households around the Poyang Lake wetland, this study analysed the influence of policies related to wetland restoration and how variables such as the cultivated land area, labour force transfer, and location of nature reserves impact farmers' income. To this end, we used a two-way fixed-effect model to test the robustness by using propensity score matching, and the influence mechanisms of wetland protection policies, such as wetland restoration, wetland ecological compensation, and the Yangtze River fishing ban, on farmers' income interactions were explored. Results and discussion The results showed that, due to the policy of wetland restoration was implemented a long time ago, the negative impact of the policy on reducing farmers' household income is not significant now. Further, farmers' family livelihood strategies have changed, and choosing other types of agricultural production and off farm employment are currently the main choices for farmers. Wetland restoration has changed their income structures. Additionally, the two wetland restoration policies and banning of fishing have had synergistic effects. The findings of this study are helpful in understanding how wetland restoration around nature reserves influences farmers' household incomes. Further, they can provide policy insights for promoting an increase in income and the optimization of the income structure of communities around lake wetland nature reserves.